A Comparison Study of the Influence of Caffeic Acid Phenethyl Ester and Mitoxantrone in Experimental Autoimmune Encephalomyelitis Balb/C Mice Model: Comparison Effect Cape and Mitoxantrone - Alnawajha, Amin; Endharti, Agustina Tri; Santoso, Sunarto; Santosaningsih , Dewi; Satriotomo , Irawan (Journal of Tropical Life Science, 2023)
A common neurodegenerative condition that still presents clinical challenges is Multiple Sclerosis (MS). Effective multiple sclerosis treatments are sorely needed in clinical settings. Experimental Autoimmune Encephalomyelitis (EAE) is an animal model of multiple sclerosis, a T-cell-mediated disease. Active T-cells differentiate into the Th9 and Th17 subsets, which are controlled by NF-kB and produce the proinflammatory cytokines IL9 and IL17. Because these cytokines are crucial to the pathophysiology of EAE, they have been used as targets for MS therapy. Caffeic acid phenethyl ester (CAPE) is an active ingredient of propolis that has been shown to have immunomodulatory and anti-inflammatory activities. Mitoxantrone is a synthetic antineoplastic agent and cytotoxic immunosuppressive effect used to treat MS. The study aimed to determine whether the two medications have superior efficacy and effect in the treatment of EAE mouse model MS compared to the other. After inducing EAE in mice, CAPE and mitoxantrone were administered to evaluate this therapeutic effectiveness. ELISA was used to measure IL9, IL17 levels and the activity of NF-kBp56. H&E was used to evaluate cell infiltration T lymphocytes for histopathology of spinal cord tissue. Molecular docking was performed to predict the interaction between CAPE and a cytokine. We found that CAPE has a sufficient effect of reducing the level of IL9, IL17, active NF-kBp56, and inflammatory cell infiltration T-lymphocytes in all groups of mice EAE treated with CAPE. In contrast, mitoxantrone reduced cytokines and cell infiltration, so EAE mice treated with both compounds were observed more improvement than other groups. Based on our findings, two medications demonstrated the same efficacy and effect in EAE mice model MS., whereas CAPE did not statistically reach a significant value. While the combination of two medications has the optimal effect.